Optimization of Higher-Order Thinking Skills (HOTS) in Islamic Education towards the Era of Society 5.0 - Wakifah, Wakifah; Fatimah, Fatimah; Sulistiawati, Mega (DIDAKTIKA, 2023)
This article aims to explore the importance of optimizing higher-order thinking Skills (HOTS) in Islamic education towards the Society 5.0 era. One of the things behind this needs to be studied because several Islamic educational institutions still apply conservative learning methods which tend to only focus on memorization and repetition of concepts, not encouraging students to think critically and creatively. The method used in preparing this article is Library Research. The results of this research show that the Society 5.0 Era is characterized by a rapid and complex technological revolution, where humans play a major role in facing global challenges and opportunities. Therefore, Islamic education must adapt and improve human quality through the application of HOTS. HOTS is a high-level thinking ability that includes analysis, evaluation, and creation. This ability is needed in facing complex problems and religious challenges in the modern era. Several HOTS-oriented Islamic education learning models have been proposed, such as Problem-Based Learning (PBL), Inquiry-Based Learning (IBL), Project-Based Learning (PjBL), and Flipped Classroom. These models require students to be active in solving problems and applying knowledge in real-life situations so that they can develop HOTS effectively.